Some Pieces Are Missing: Implicature Production in Children - Eiteljoerge, Sarah F. V.; Pouscoulous, Nausicaa; Lieven, Elena V. M. (Frontiers in Psychology, 2018)
Until at least 4 years of age, children, unlike adults, interpret some as compatible with all. The inability to draw the pragmatic inference leading to interpret some as not all, could be taken to indicate a delay in pragmatic abilities, despite evidence of other early pragmatic skills. However, little is known about how the production of these implicature develops. We conducted a corpus study on early production and perception of the scalar term some in British English. Children’s utterances containing some were extracted from the dense corpora of five children aged 2;00 to 5;01 (N = 5,276), and analysed alongside an equivalent portion of their caregivers’ utterances with some (N = 9,030). These were coded into structural and contextual categories allowing for judgments on the probability of a scalar implicature being intended. The findings indicate that children begin producing and interpreting implicatures in a pragmatic way during their third year of life, shortly after they first produce some. Their production of some implicatures is low but matches their parents’ input in frequency. Interestingly, the mothers’ production of implicatures also increases as a function of the children’s age. The data suggest that as soon as they acquire some, children are fully competent in its production and mirror adult production. The contrast between the very early implicature production we find and the relatively late implicature comprehension established in the literature calls for an explanation; possibly in terms of the processing cost of implicature derivation. Additionally, some is multifaceted, and thus, implicatures are infrequent, and structurally and contextually constrained in both populations.